The Multy Actors’s Role in Implementation Policy ProcessMulty Actors’s Role in Implementation Policy Process (Case Study in Policy of Compulsory Basic Education 12 Years at Kudus Regency, Central Java, Indonesia) - Asih Widi Lestari; Sri Suwitri; Endang Larasati; Hardi Warsono (NAROTAMA UNIVERSITY, Indonesia, 2020)
Kudus Regency is one area that successfully implemented Policy of Compulsory Basic Education 12 years since 2010 even before the central government issued a Policy of Compulsory Basic Education 12 years. In implemented this policy, Kudus Regency Government based on the Kudus Regency Regulation Number 2/ 2010 about Basic Education 12 Years and Regulation of Minister Education and Culture Republic Indonesia Number 80/2013 about Universal Secondary Education (Basic Education 12 Years). The success of Kudus Regency in implementing compulsory basic education 12 years policy is depending on the role of actors that depending in the implementation process. This research is using descriptive qualitative approach. The results of this research is the successful implementation of compulsory basic education 12 years policy in Kudus Regency can not be sparated from the synergy of multyactors’s role. The role of Central Government and Kudus Regency Government that is by issuing compulsory basic education 12 years policy, i. e Regulation Minister of Education and Culture Number 80/2013 and Kudus Regency Regulation Number 2/2010 about compulsory basic education 12 years, and their programs support. The private sector’s roles, is by providing scholarships and grants to infrastructure development of schools in Kudus Regency. The role of Kudus Regency society is provide full support and enthusiasm in implementing compulsory basic education in Kudus Regency.